Penguatan Kapabilitas Kader Posyandu melalui Pelatihan Antropometri untuk Deteksi Dini Masalah Gizi Stunting - Monikasari, Monikasari -; Mangalik, Gelora; Davidson, Sarah Melati; Renyoet, Brigitte Sarah; Nugroho, Kristiawan Prasetyo Agung (Jurnal Abdimas Kesehatan (JAK), 2024)
Stunting is a condition where a child’s body is too short for age. Stunting can occur due to insufficiency of most of the necessary nutrients and/or due to recurrent infections in the first 1000 days of a child’s life. Handling and preventing stunting requires the role and cooperation of parents, the community and the government. The community can play a role in handling and preventing stunting through involvement as posyandu cadres. Posyandu cadres as health workers accompany puskesmas health workers in carrying out early detection, treatment and prevention of stunting. The aim of this community service is to improve the skills of posyandu cadres regarding anthropometric measurements. The method of community service carried out is a pre-test, presenting the subject matter, cadres practicing anthropometric measurements and post-tests carried out on posyandu cadres in nine villages in Boyolali Regency, namely Selodoko Village, Sidomulyo Village, Repaking Village, Gilirejo Village, Semawung Village, Pranggong Village, Sambeng Village, Kalimati Village, Juwangi Village. The result of this community service was an increase in the knowledge and skills of posyandu cadres, before the community service activities were carried out the average pre-test score was 58.1 and after the community service activities were carried out the average post-test score was 67.8. Increased knowledge of 9.6. It was concluded that after education and training, posyandu cadres could understand how to carry out good and correct anthropometric measurements. It is hoped that the government can play a role in providing regular education and training to refresh knowledge and anthropometric measurements.